Penerapan Prinsip Kehati-Hatian Notaris Ketika Membuat Akta Perjanjian Perkawinan Pisah Harta - Rachmawati, Risa; Safa'at, Rachmad; Navianto, Isma'il (Lentera Hukum, 2015)
The decision of the Constitutional Court Number 69/PUU-XIII/2015, meaning that the marriage agreement is no longer as a treaty made before marriage but may also be made during the marriage association, which was previously restricted by article 29 paragraph (1) of the marriage law that the marriage agreement was made after the marriage. However, the issuance of the decision of the Court MK Number 69/PUU-XIII/2015 without being followed by the implementing regulation resulted in practice there are many misunderstandings of understanding and the difference of legal application among the notary especially the notary of Malang city about the making of the deed. This shows the gap between the rules regarding the making of marriage agreement with the practice in society so that there are obstacles in the implementation of the law. This method used is the type of empirical legal research using the approach of legal sociology. As the results of this study indicate: first, that the notary must prioritize the principle of caution because there are still some legal issues related to the making of the marriage certificate of separation of property during the marriage bond in the mixed marriage after the decision of the Court MK Number 69/PUU-XIII/2015. Second, legal liability if the notary ignores the precautionary principle, may be liable for the deeds he or he has made, as well as the actions of the notary. Third, the application of prudential principles to the process of making marriage certificate deeds during the marriage must comply with the elements of article 1320 KUHPerdata (BW) and UUJN. KEYWORDS: Prudential Principle, Notary, Postnuptial Agreement, During Marital Bond, Intermarriage.